Optically-generated focused ultrasound for noninvasive brain stimulation with ultrahigh precision - Yueming Li; Ying Jiang; Lu Lan; Xiaowei Ge; Ran Cheng; Yuewei Zhan; Guo Chen; Linli Shi; Runyu Wang; Nan Zheng; Chen Yang; Ji-Xin Cheng (Light: Science & Applications, 2022)
We report optically-generated focused ultrasound for non-invasive brain stimulation with ultrahigh precision of 83 µm, which is two orders of magnitude smaller than that of conventional transcranial focused ultrasound.